Kemampuan Membaca Anak Menggunakan Permainan Ular Tangga Kata di Taman Kanak-Kanak Kemala Bhayangkari 1 Padang - Syahputri, Fina; Yulsyofriend, Yulsyofriend (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to find out how the snake and ladder word game influences children's reading ability at Kindergarten Kemala Bhayangkari 1 Padang. This type of research combines quasi-experimental methodology with a quantitative approach. This research was conducted at Kindergarten Kemala Bhayangkari 1 Padang. All children in Kindergarten Kemala Bhayangkari 1 Padang were used as the research population, and 10 children in each group B2 and B3, which functioned as the control class and experimental class were used as samples. Oral tests are the method researchers use to collect data. Normality test, homogeneity test, and hypothesis test are the data analysis techniques used. Data analysis shows that the average pre-test score for the experimental group is 16.2 and the post-test score is 18.2. The average pre-test result for the control class was 14.7 and the post-test result was 15.6. The final data set is homogeneous and regularly distributed. Based on the results of the hypothesis test showing a sig (2-talied) value of 0.020 < 0.05, it can be concluded that the snake and ladder word game affects children's reading ability at Kindergarten Kemala Bhayangkari 1 Padang.